What integrated care means from an older person’s perspective? A scoping review protocol - Amy Marshall; Manasi Murthy Mittinty; Gillian Harvey (BMJ Open)
Introduction According to the 2013 WHO Global Forum on Innovation for Ageing Populations, disabilities and morbidities associated with ageing could be minimised by accessing preventive care. One way of improving the management of multimorbidity in the older population is through the provision of ‘integrated care’. Although integrated care means different things to different people, it typically symbolises continuity in care, thus preventing older patients' from falling through gaps in the health care system. Many initiatives have attempted to improve the integration of care; however, these are typically designed from a particular policy or system perspective. Relatively little is known about patient expectations and experiences of integrated care, which is vital for developing and implementing better models of care. The proposed scoping review aims to map literature on older patients'’ views, expectations, experiences and perspectives of integrated care.Methods and analysis Multiple electronic databases including PubMed, Web of Science, Embase, PsychInfo, Google Scholar, Cochrane Library, CINAHL and ProQuest Dissertations will be searched for appropriate articles between August and December 2017. Reference lists of selected articles will also be searched for similar articles. Two experienced researchers will conduct an initial search of the literature to identify relevant articles. Abstracts of the identified articles will be reviewed collectively by two researchers to identify potential further studies. Full texts of the potential studies will be sourced and screened for the inclusion criteria. Appropriate qualitative and quantitative methods will be used to extract data from each included study.Ethics and dissemination The scoping review will synthesise findings from studies reporting on patients’ views and expectations of integrated care. This review expects to find information relating to facilitators and barriers of integrated care from an older person’s perspective. The findings from the review will be applied when working with stakeholders representing older people, healthcare, aged care and community providers, researchers and policy makers to develop and evaluate a more locally tailored and person-centred approach to integrated care.